2018
DOI: 10.17977/um002v10i12018p035
|View full text |Cite
|
Sign up to set email alerts
|

Farmer Exchange Rate and Agricultural Land Conversion Analysis to Agricultural Sector Poverty in Indonesia

Abstract: The agricultural sector poverty in Indonesia is affected by some factors like income and agricultural land area. Farmer exchange rate is an indicator of farmer welfare that can be a measurement of farmer real income. Farmer exchange rate tends to be increased from 2009 to 2013. Besides, the agricultural land area tends to decrease that time. Decreasing of agricultural land is caused by agricultural land usage conversion. This research aims to analyze direct and indirect effects of farmer exchange rate and agri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 4 publications
0
6
0
1
Order By: Relevance
“…The fluctuations in the farmer exchange rates are also indicated by changes in regional gross domestic product and economic growth at the national level. The rate has a direct and indirect effect on farmer poverty (Setiyowati et al 2018). Our analysis of the ten provinces concluded that the highest rate was in Riau, and the lowest in Nangro Aceh Darussalam.…”
Section: Conclusion and Recomendations 51 Conclusionmentioning
confidence: 73%
See 4 more Smart Citations
“…The fluctuations in the farmer exchange rates are also indicated by changes in regional gross domestic product and economic growth at the national level. The rate has a direct and indirect effect on farmer poverty (Setiyowati et al 2018). Our analysis of the ten provinces concluded that the highest rate was in Riau, and the lowest in Nangro Aceh Darussalam.…”
Section: Conclusion and Recomendations 51 Conclusionmentioning
confidence: 73%
“…We divided previous studies into two main topics: the farmer exchange rate and the consumer confidence index regarding the monetary sector. Research conducted by Setiyowati, Sasongko, & Noor (2018) found that the farmer exchange rate is an indicator of farmers' welfare and can be a measurement of their real income (Setiyowati et al 2018;Syekh, 2013). The Indonesian farmer exchange rate tended to increase from 2009 to 2013.…”
Section: Previous Studiesmentioning
confidence: 99%
See 3 more Smart Citations